2017
DOI: 10.1039/c7tb00341b
|View full text |Cite
|
Sign up to set email alerts
|

The physics and chemistry of silica-in-silicates nanocomposite hydrogels and their phycocompatibility

Abstract: aSilicates-in-silica nanocomposite hydrogels obtained from sodium silicates/colloidal silica mixtures have previously been found to be useful for bacterial encapsulation. However the extension of synthesis conditions and the understanding of their impact on the silica matrix would widen the applicability of this process in terms of encapsulated organisms and the host properties. Here the influence of silicates and the colloidal silica concentration as well as pH conditions on the gel time, the optical properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…Here, the metal ions occur as by-products. Commonly applied sodium silicate concentrations of 1.06–19 wt % resulted in sodium ion concentrations of 0.64 to 18.8 mol/L [ 41 , 42 , 97 , 98 , 124 , 129 , 130 , 164 , 165 ]. It has already been applied for the entrapment of the microalgae Chlorella vulgaris , Dictosphaerium chlerelloides , Scenedesmus intermedius , Scenedesmus sp., Mesotaenium sp., and Cyanidium caldarium as well as the euglenoid Euglena gracilis and the cyanobacteria Anabaena flos-aqua , Synechococcus sp., and Cyanothece [ 41 , 97 , 98 , 124 , 129 , 130 ].…”
Section: Entrapment Of Microalgae In Silica Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the metal ions occur as by-products. Commonly applied sodium silicate concentrations of 1.06–19 wt % resulted in sodium ion concentrations of 0.64 to 18.8 mol/L [ 41 , 42 , 97 , 98 , 124 , 129 , 130 , 164 , 165 ]. It has already been applied for the entrapment of the microalgae Chlorella vulgaris , Dictosphaerium chlerelloides , Scenedesmus intermedius , Scenedesmus sp., Mesotaenium sp., and Cyanidium caldarium as well as the euglenoid Euglena gracilis and the cyanobacteria Anabaena flos-aqua , Synechococcus sp., and Cyanothece [ 41 , 97 , 98 , 124 , 129 , 130 ].…”
Section: Entrapment Of Microalgae In Silica Hydrogelsmentioning
confidence: 99%
“…Moreover, the authors argued that the nanoparticles are small enough to be potentially internalized [ 42 ]. This effect seems to be species-specific, as other microalgae and cyanobacteria show cell activity in LUDOX ® -reinforced silica hydrogels [ 97 , 98 , 124 , 129 , 130 , 164 , 165 ]. It was discussed that observed harmful effects of elevated LUDOX ® concentrations from 1 to 3 mol/L on entrapped Anabaena flos-aquae could be caused by an increased Young’s modulus [ 130 ].…”
Section: Entrapment Of Microalgae In Silica Hydrogelsmentioning
confidence: 99%
“…Depending on the composition, the transmittance of nanocomposite gels may also be sensitive to pH variations. For example, Ahmed and co-authors [ 105 ] showed that nanocomposite hydrogels obtained from sodium silicates/colloidal silica mixtures, developed for bacterial encapsulation, lost transparency when lowering the pH from 7 to 5 (as well as the ability to gel) when using Ludox silica particles, while sodium silicate NPs showed the opposite trend, with samples becoming more opaque when the pH was increased from 5 to 6. The authors concluded that the transparency variations were related to NP aggregation upon pH variation and that by varying the pH and NP concentration, whose increase resulted in an increase in optical density, it was possible to synthesize gels with a similar transparency for a wide range of silicate concentrations [ 105 ].…”
Section: Nanoparticles For Improving Hydrogel Propertiesmentioning
confidence: 99%
“…Nanocomposite hydrogels have been shown to exhibit an increase of both shear storage modulus ( G ’) [ 59 , 68 , 74 , 103 , 112 , 113 , 114 , 115 ] and Young’s modulus ( E ) [ 52 , 59 , 102 , 103 , 105 , 107 , 109 , 114 , 115 , 116 ] in comparison to covalently cross-linked hydrogels with a similar polymer composition prepared with some form of cross-linking agent (for example N , N ′-methylenebis(acrylamide)) [ 59 , 109 ]. However, as previously mentioned, the covalently cross-linked gels generally have a higher cross-linking density [ 109 ], which might justify, at least partially, the different behavior of the materials.…”
Section: Nanoparticles For Improving Hydrogel Propertiesmentioning
confidence: 99%
See 1 more Smart Citation